KEBIJAKAN PEMIMPIN DALAM EFEKTIVITAS KERJA PEGAWAI PADA PT HASJRAT ABADI KOTA SORONG - Moh. Saleh Refra (JIA: Jurnal Ilmiah Administrasi, 2021)
This study aims to find out how, obstacles and efforts and problem solving on the work effectiveness of employees at PT Hasjrat Abadi Sorong City. The research method using qualitative. Data analysis techniques, the data collected in this study, both primary data and secondary data were re-examined in order to determine the completeness of the data obtained. The results of this study indicate that the leader's policy on employee work effectiveness is very important with good communication, direction and guidance providing opportunities and confidence in carrying out work effectiveness in the company, vision and mission, environment and intimacy. The way to solve the problem of the leader's policy in the effectiveness of employee work is to conduct various direct opinions, create a good working atmosphere and relationship, provide work support facilities and infrastructure and establish good cooperation between leaders and employees.